2022
DOI: 10.7150/ijbs.63876
|View full text |Cite
|
Sign up to set email alerts
|

Specific overexpression of SIRT1 in mesenchymal stem cells rescues hematopoiesis niche in BMI1 knockout mice through promoting CXCL12 expression

Abstract: Osteoblastic lineage cells (OBCs) are bone-building cells and essential component of hematopoietic niche, but mechanisms whereby bone-building and hematopoiesis-supportive activities of OBCs could be regulated simultaneously remain largely unknown. Here we found that B cell-specific Moloney murine leukemia virus integration site 1 (Bmi1) was involved in such a co-regulatory mechanism. In this study, we first found that, accompanied with marked decline of osteogenic activity, the hematopoietic niche in Bmi1 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…MiR-30b-5p overexpression could reduce intracellular lipid deposition and regulate intracellular lipid metabolism by targeting PPAR-α and GLUT1, thus triggering mitochondrial oxidative phosphorylation, fatty acidbeta-oxidation and synthesis, glucose uptake, and gluconeogenesis. Also, the mucin-type O-glycan biosynthesis pathway (pathway 2) appears solely associated with hsa-miR-30b-5p, which controls a group of isoenzymes that initiate several glycosylation reactions [48][49][50]. Aberrant expression of glycan has been reported in most hematological malignancies, such as AML, myeloproliferative neoplasms, and multiple myeloma, as well in bone-marrow-associated breast cancer cell dissemination [51][52][53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-30b-5p overexpression could reduce intracellular lipid deposition and regulate intracellular lipid metabolism by targeting PPAR-α and GLUT1, thus triggering mitochondrial oxidative phosphorylation, fatty acidbeta-oxidation and synthesis, glucose uptake, and gluconeogenesis. Also, the mucin-type O-glycan biosynthesis pathway (pathway 2) appears solely associated with hsa-miR-30b-5p, which controls a group of isoenzymes that initiate several glycosylation reactions [48][49][50]. Aberrant expression of glycan has been reported in most hematological malignancies, such as AML, myeloproliferative neoplasms, and multiple myeloma, as well in bone-marrow-associated breast cancer cell dissemination [51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant expression of glycan has been reported in most hematological malignancies, such as AML, myeloproliferative neoplasms, and multiple myeloma, as well in bone-marrow-associated breast cancer cell dissemination [51][52][53]. The mucin-type O-glycan biosynthesis pathway links glucose dysmetabolism and type 2 diabetes [54], a well-established phenotypic feature in FA disease, associated with redox unbalance and mitochondrial dysfunctionality [49,50,54].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, SIRT1 regulates the cell cycle of macrophages and longevity pathways; in addition, it favors the polarization of macrophages toward the M2 phenotype by reducing TNF-α and IL-1β [40,41]. On the other hand, SIRT1 influences the stroma that supports hematopoiesis, since in mesenchymal stem cells (MSCs), it promotes the expression of CXCL12 by inhibiting p53 activation, thus favoring the recovery of the hematopoietic niche [42].…”
Section: Sirt1 In Normal Hematopoiesismentioning
confidence: 99%
“…Leko et al showed that SIRT1 does not play an essential role in the maintenance of the HSC compartment in adult C57BL/6 mice, and deletion did not affect HSC maintenance and long-term reconstitution in adult mice in the steady state [34]. Additionally, SIRT1 inhibition has only a minor impact on normal human CD34+ hematopoietic cells [42]; thus, the role of SIRT1 in adult HSCs is still controversial. The basis of this difference in the apparent importance of SIRT1 in adult mouse hematopoiesis could be found in the C57BL/6 mouse model.…”
Section: Sirt1 In Normal Hematopoiesismentioning
confidence: 99%

Role of SIRT1 in Chemoresistant Leukemia

Fajardo-Orduña,
Ledesma-Martínez,
Aguiñiga-Sanchez
et al. 2023
IJMS